2019
DOI: 10.1097/prs.0000000000005453
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Masculinizing Gender Surgery

Abstract: Learning Objectives: After reading this article and viewing the video, the participant should be able to: 1. Discuss appropriate treatment guidelines, including preoperative mental health and hormonal treatment before gender-affirmation surgery. 2. Name various surgical options for facial, chest, and genital masculinization. 3. Recognize key steps and anatomy during chest-wall contouring and phalloplasty reconstruction. 4. Discuss major risks and complications of chest-wall contouring and phallopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…It then travels distally with the cephalic vein towards the 1st and 2nd extensor compartments of the wrist [18,19] . The RFF's reliable neurovascular anatomy, including its innervation density, and its thin subcutaneous fat layer (helpful for flap shaping and a double tube procedure) make it a frequent "first-choice" option for phalloplasty [ Figure 2] [7,10,[20][21][22][23][24][25][26] . However, color mismatch, atrophy over time, and a conspicuous donor site may lead some individuals to select other flap options [7,10,20,21,24,27,28] .…”
Section: Current Phalloplasty Flap Optionsmentioning
confidence: 99%
See 3 more Smart Citations
“…It then travels distally with the cephalic vein towards the 1st and 2nd extensor compartments of the wrist [18,19] . The RFF's reliable neurovascular anatomy, including its innervation density, and its thin subcutaneous fat layer (helpful for flap shaping and a double tube procedure) make it a frequent "first-choice" option for phalloplasty [ Figure 2] [7,10,[20][21][22][23][24][25][26] . However, color mismatch, atrophy over time, and a conspicuous donor site may lead some individuals to select other flap options [7,10,20,21,24,27,28] .…”
Section: Current Phalloplasty Flap Optionsmentioning
confidence: 99%
“…Pedicled flap options Radial forearm flap [7,8,10,11,[20][21][22][23][24][25][26][27][28]68] Anterolateral thigh flap [7,20,21,23,34,35,68] Anterolateral thigh flap [7,21] Abdominal flaps [7,21] Osteocutaneous fibula flap [7,27,42,70] Groin flap [7] Musculocutaneous latissimus dorsi flap [40,41] Gracilis flap [7] Lateral arm flap [10,66] Superficial circumflex iliac artery perforator flap [45][46][47] patients reported tactile sensation, and 71.4% of patients reported the return of erogenous sensation. Monstrey et al [24] found that all patients regained tactile sensitivity 1 year following RFF phalloplasty.…”
Section: Free Flap Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, restoration of cutaneous sensation in the phallus is always via straightforward nerve coaptation between a cutaneous nerve of the flap and a sensory nerve in the recipient site. This aspect of phalloplasty has been well covered in detail in two recent reviews and we will not elaborate further here [22][23][24] .…”
Section: Tactile and Erogenous Sensationmentioning
confidence: 99%